PENGUATAN RASA CINTA TANAH AIR DALAM BUDAYA LOKAL KEGIATAN SENI JARANAN SENTEREWE DI SANGGAR CAKRA AJI TULUNGAGUNG - Lutfi Kharisma Yogi; Dirgantoro , Ajar; Andrie Djatmiko, Andreas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the representation of patriotism through the art of Jaranan Senterewe at Sanggar Cakra Aji Tulungagung and to examine the process of internalizing patriotic values among the members of the art community. The study is motivated by the importance of preserving local culture as a means of strengthening character and national identity amid the challenges of globalization that affect younger generations. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, in-depth interviews, and documentation. The research informants consisted of the head of the art studio, instructors, and members of Sanggar Cakra Aji Tulungagung. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using Hans Kohn's theory of cultural nationalism, value internalization theory, and culture-based character education theory. The findings indicate that patriotism is represented through pride in local culture, participation in cultural preservation, cooperation, discipline, and active involvement in Jaranan Senterewe activities. The process of value internalization occurs through the stages of introduction, understanding, appreciation, and implementation. Sanggar Cakra Aji functions as a non-formal educational space that instills national values and character among its members. The findings support the theory of cultural nationalism, which emphasizes the important role of local culture in shaping national identity and national consciousness.